Land Titling and Class Relations Among the Maguindanaos of Ligawasan Marsh: Implications for Peace and Development - Gatmaytan, Augusto B. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
The Ligawasan Marsh Stakeholders Mapping Project of 2014 elicited the views of Maguindanao fishers and farmers on the feasibility and possible consequences of establishing a protected area that would cover the Ligawasan Marsh area. In general, there was broad but qualified approval of this project. One of the conditions for accepting the proposed protected area plan was fair implementation of the project. This study traces this concern for fairness to historical experiences of economic marginalization, by the more powerful or elite Maguindanao families, particularly with regard to landownership. The data also shows that many informants sought the Moro Islamic Liberation Front’s involvement in the future management of the marsh. This suggests that non-elite Maguindanaos look to the Moro Islamic Liberation Front to control elite Maguindanao families who may seek to exploit the opportunities offered by the establishment of a protected area in the Ligawasan marsh, or by growing foreign investments on oil palm production in the area.
Keywords: ancestral domain, class relations, Ligawasan Marsh, Maguindanao, Moro Islamic Liberation Front